Increasing Family Capacity in Self-Care Management of Heart Failure Patients at the Heart Polyclinic of RSUD dr. Slamet Garut (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Heart failure is one of the leading causes of decreased quality of life and increased hospitalization rates in Indonesia. Effective self-care, including medication adherence, diet management, and symptom monitoring, is crucial in preventing complications. Many patients and families have limited knowledge and skills in self-care. Family involvement as a key supporter has been shown to improve patient health outcomes. Therefore, educational efforts are needed to increase family capacity in heart failure patients’ self-care. To achieve this capacity, a community service activity was organized that aims to improve family knowledge and skills in caring for heart failure patients. The activity took the form of structured education at the heart polyclinic of RSUD Dr. Slamet Garut, which was attended by 20 people. The pre and post-test results showed an increase in family capacity in self-care of heart failure patients. Thus, the activities carried out are useful for increasing family capacity in the self-care of heart failure patients. This activity is expected to continue to be carried out in other similar cases to improve quality of life.